The Dermoscopic Features of Photoaging and Its Association with Sun Index Score in the Coastal Population at Cilincing, Jakarta: A Cross-Sectional Study - Respati RA; Yusharyahya SN; Wibawa LP; Widaty S (Dove Medical Press, 2022)
Riris Asti Respati, Shannaz Nadia Yusharyahya, Larisa Paramitha Wibawa, Sandra Widaty Department of Dermatology and Venereology, Faculty of Medicine Universitas Indonesia - Dr. Cipto Mangunkusumo Hospital, Jakarta, IndonesiaCorrespondence: Shannaz Nadia Yusharyahya, Department of Dermatology and Venereology, Faculty of Medicine Universitas Indonesia - Dr. Cipto Mangunkusumo Hospital, 71 Diponegoro, Jakarta, Indonesia, 10430, Tel +62 131935383, Email nadiayusharyahya@yahoo.comPurpose: Repeated exposure to ultraviolet light is the most significant factor that contributes to photoaging. Dermoscopy photoaging scale (DPAS) is a noninvasive examination utilized for the diagnosis of photoaging. However, there has been no study analyzing the correlation between DPAS and sun index. Hence, this study aims to find out the dermoscopic features of photoaging and its association with sun index score in the coastal population.Patients and Methods: This was a descriptive cross-sectional study on individuals living in Cilincing, a coastal area, at North Jakarta. Healthy male or female subjects aged over 18 years old with sun exposure equal or more than 2 hours daily were recruited consecutively. History taking was performed to document the sociodemographic characteristics (age, gender, skin type, smoking habit) and sun index score. Physical examination and dermoscopic examination were conducted to determine DPAS score. Associations of DPAS and photoaging profiles were analyzed with Chi-squared test while correlation between DPAS score and sun index was analyzed with Pearson correlation test.Results: A total of 100 subjects were included in this study. The median DPAS of the subjects was 9 (1- 21). Right cheek had the highest median DPAS of 3 (0- 6), followed by the left cheek with median DPAS of 3 (0- 7). Men had a higher median DPAS score than women (9 vs 8). There was a significant difference between DPAS score and age (p< 0.001). There was no significant correlation between DPAS score and sun index (r = − 0.005; p = 0.957).Conclusion: Factors associated with high DPAS score were cheek predilection, male, actively smoking, Fitzpatrick skin type IV, and increasing age. DPAS score has no correlation with sun index.Keywords: dermoscopy, photoaging, sun index, coastal area